Two novel Raoultella species associated with bleeding cankers of broadleaf hosts, Raoultella scottia sp. nov. and Raoultella lignicola sp. nov. - Brady, Carrie; Crampton, Bridget; Kaur, Sundeep; Maddock, Daniel; Kile, Helene; Arnold, Dawn; Denman, Sandra (Frontiers in Microbiology, 2024)
Seventeen Gram-negative, facultatively anaerobic bacterial strains were isolated from bleeding cankers of various broadleaf hosts and oak rhizosphere soil in Great Britain. The strains were tentatively identified as belonging to the genus Raoultella based on 16S rRNA gene sequencing. Multilocus sequence analysis (MLSA), based on four protein-encoding genes (fusA, leuS, pyrG and rpoB), separated the strains into three clusters within the Raoultella genus clade. The majority of strains clustered with the type strain of Raoultella terrigena, with the remaining strains divided into two clusters with no known type strain. Whole genome sequencing comparisons confirmed these two clusters of strains as belonging to two novel Raoultella species which can be differentiated phenotypically from their current closest phylogenetic relatives. Therefore, two novel species are